ANALISIS KEMAMPUAN BERPIKIR SAINTIFIK PESERTA DIDIK SD PADA SOAL OPEN ENDED DITINJAU DARI GENDER - Maharani, Suci; Nugraha, Akhmad; Ramadhani Putri, Agnestasia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the scientific thinking abilities of male and female students in solving open-end questions. This research was designed using qualitative research with exploratory methods. The data collection techniques used in this research were observation, test questions, interviews, and documentation. From the results of this research it can be concluded that 1) There is no difference in the scientific thinking abilities of male and female students in the high group, but there is a difference in scientific attitudes, namely female students in the high group do not show respect for data/facts. 2) There are differences in the scientific thinking abilities of male and female students in the medium group. Male students are able to carry out investigations, analyze and make inferences. Meanwhile, female students are able to analyze and provide arguments. Male students show a curious attitude, respect for data/facts, a critical thinking attitude, an open-minded attitude and cooperation, perseverance and a sensitive attitude towards the surrounding environment. Where female students show respect for data/facts, open thinking and cooperation and are sensitive to the surrounding environment. 3) There are differences in the scientific thinking abilities of male and female students in the low group. Male students are able to carry out investigations and make inferences. Meanwhile, female students are only able to provide arguments. Then there are differences in scientific attitudes shown by male and female students in the low group. Male students show discovery and creativity, an open-minded attitude and cooperation and a sensitive attitude towards the surrounding environment. Where female students show an attitude of curiosity, respect for data/facts, an attitude of discovery and creativity as well as an open mind and cooperation. Keywords: gender, open ended, scientific